(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
The capacity of students to communicate mathematical ideas mathematically is one area in which it is crucial to focus. The definition of mathematical communication abilities, metrics for assessing mathematical communication abilities, and learning models that are meant to enhance students’ mathematical communication abilities are the main goals of this research. Systematic Literature Review (SLR) is the methodology employed. Data was gathered by recording and going over every publication about mathematical communication abilities that contained research that was comparable to this study. This study used twenty publications that were found on DOAJ, Research Gate, Science Direct, and Google Scholar. The research underscores the critical importance of diverse factors in enhancing mathematical communication skills, including collaborative learning, teacher feedback, cultural awareness, digital tools, language proficiency, rubric-based assessments, and more. Collaborative learning stands out as notably effective, positively influencing students’ capacity to articulate and defend mathematical reasoning through peer debates. Teachers’ prompt and constructive feedback contributes to the lucidity and accuracy of students’ mathematical explanations. Recognizing cultural diversity fosters inclusivity and enhances the sharing of mathematical concepts, while the use of digital tools enables alternative means for expression and collaboration. The complex relationship between language development and mathematical communication abilities is emphasized, highlighting the need for ongoing growth and a comprehensive, inclusive strategy for the future of mathematics education and communication.